A plain language summary of the CAPItello-291 study: Capivasertib in hormone receptor-positive advanced breast cancer - Turner, NC (2024)
What is this summary about?: This is a summary of the article discussing the results of the CAPItello-291 study. In the study, participants had advanced breast cancer that could not be completely removed with surgery, and that was diagnosed as a type of breast cancer where tumor cells had hormone receptors (HR-positive) but did not have HER2 receptors (HER2-negative). All participants were also required to have previously received treatment with a type of therapy called an aromatase inhibitor (with or without a CDK4/6 inhibitor), but over time their cancer cells had still grown or spread. The CAPItello-291 study researchers wanted to find out if a treatment combination of the medications capivasertib plus fulvestrant worked better than placebo plus fulvestrant. Capivasertib is a drug that blocks the activity of a protein called AKT, which is found inside breast cancer cells. What are the key takeaways?: The main finding was that participants who took capivasertib plus fulvestrant lived longer without their disease getting worse (progressing) compared with those treated with placebo plus fulvestrant. This is called progression-free survival. This result was seen across all participants (median progression-free survival of 7.2 months with capivasertib plus fulvestrant vs 3.6 months with placebo plus fulvestrant). It was also seen in participants whose tumors had detectable genetic alterations in genes called PIK3CA, AKT1, and/ or PTEN (median progression-free survival of 7.3 months with capivasertib plus fulvestrant vs 3.1 months with placebo plus fulvestrant). The most common side effects experienced by participants included diarrhea and different types of rash. These were as expected (given how capivasertib works). The CAPItello-291 study is still ongoing, and more results are expected to be released in the future. What were the main conclusions reported by the researchers?: Results from the CAPItello-291 study showed that capivasertib plus fulvestrant compared with placebo plus fulvestrant improved progression-free survival in participants with HR-positive/ HER2-negative advanced breast cancer whose cancer had grown or spread despite hormone therapy (with/without a CDK4/6 inhibitor). Clinical Trial Registration:NCT04305496 (CAPItello-291) (ClinicalTrials.gov).